Analysis Of Factors Affecting the Human Development Index (HDI) in Singapore from 1998-2023 - Farid, Muhammad; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This quantitative study aims to examine the impact of the elements that make up the Human Development Index (HDI)-which consists of Health (Life Expectancy), Education (Average Length of Schooling), and Standard of Living (Gross National Income)-on the HDI in Singapore from 1998 to 2023. Using time series data and applying econometric regression models, this study shows that these three aspects have a significant and positive contribution to HDI improvement. These findings confirm that Singapore's HDI, which has consistently been in the Very High category, is driven by successful investments in planned human capital development. The Health and Education variables have been proven to play an important role in maintaining the rate of HDI growth, reinforcing the view that sustainable human development is the key to national welfare and long-term economic resilience.